Prologue First Edition Morpheús (MORPHEÚS: Digital Journal of Pfychology of the Marista University of Queretaro, 2024)
The publication MORPHEÚS: Digital Journal of Psychology of the Universidad Marista de Querétaro is the result of a joint effort between the academic and administrative staff of the MUQ Faculty of Psychology, with the valuable support of the Faculty of Design and the Queretaro Normal School, ensuring the quality and excellence of the content presented. With this first issue, MORPHEÚS aims to establish itself as a prestigious academic journal, with the purpose of significantly contributing to the development of knowledge in the field of psychology, both nationally and internationally.We cordially invite you to explore this first issue and continue promoting the exchange of ideas among professionals.